The emerging role of TET enzymes in the immune microenvironment at the maternal-fetal interface during decidualization and early pregnancy - Jin, Mengmeng; Ji, Jianxiong; Chen, Xi; Zhou, Ying; Wang, Dimin; Liu, Aixia (Frontiers in Immunology, 2023)
A dysregulated immune microenvironment at the maternal-fetal interface in early pregnancy may lead to early pregnancy loss, fetal growth restriction, and preeclampsia. However, major questions about how epigenetic modifications regulate the immune microenvironment during the decidualization process and embryo implantation remain unanswered. DNA methylation, the main epigenetic mechanism involved in the endometrial cycle, is crucial for specific transcriptional networks associated with endometrial stromal cell (ESC) proliferation, hormone response, decidualization, and embryo implantation. Ten-eleven translocation (TET) enzymes, responsible for catalyzing the conversion of 5-methylcytosine to 5-hydroxymethylcyosine, 5-formylytosine, and 5-carboxylcyosine to achieve the DNA demethylation process, appear to play a critical role in decidualization and embryo implantation. Here, we provide a comprehensive view of their structural similarities and the common mechanism of regulation in the microenvironment at the maternal-fetal interface during decidualization and early pregnancy. We also discuss their physiological role in the decidual immune microenvironment. Finally, we propose a key hypothesis regarding TET enzymes at the maternal-fetal interface between decidual immune cells and ESCs. Future work is needed to elucidate their functional role and examine therapeutic strategies targeting these enzymes in pregnancy-related disease preclinical models, which would be of great value for future implications in disease diagnosis or treatment.